2014
DOI: 10.1007/s12560-014-9177-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV Light on the Inactivation of Recombinant Human Adenovirus and Murine Norovirus Seeded in Seawater in Shellfish Depuration Tanks

Abstract: Shellfish depuration is a process that aims to eliminate pathogens from mollusk tissues. Seawater disinfection during the depuration process is important and ultraviolet (UV) light treatment is the most used method worldwide. Viral models are usually employed as surrogates of fastidious viruses in viability studies. The aim of this study was to employ methods based on green fluorescent protein (GFP) fluorescence and plaque forming units to detect, respectively, recombinant adenovirus (rAdV-GFP) and murine noro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Using an animal cell line assay, UV treatment has been shown to reduce NoV surrogates to non-infectious levels (Garcia et al 2015; Neish 2013). Typically, however, water temperature was elevated in these experiments and therefore the relevance to human infectivity is thought to be limited (Cook et al 2015).…”
Section: Regulating Nov In Shellfish Waters and Shellfish: Current Prmentioning
confidence: 99%
“…Using an animal cell line assay, UV treatment has been shown to reduce NoV surrogates to non-infectious levels (Garcia et al 2015; Neish 2013). Typically, however, water temperature was elevated in these experiments and therefore the relevance to human infectivity is thought to be limited (Cook et al 2015).…”
Section: Regulating Nov In Shellfish Waters and Shellfish: Current Prmentioning
confidence: 99%
“…Historically, these standards (27)(28)(29)(30) have succeeded in reducing many types of shellfishrelated bacterial outbreaks; however, it has been shown that the bacterial standards are inadequate for estimating the presence of enteric viruses in shellfish and growing waters. Moreover, the depuration process for shellfish harvested from conditionally approved (or category B) growing areas has been shown to be less effective at eliminating enteric viruses than bacteria from contaminated shellfish (31)(32)(33). Therefore, it is necessary to understand the interaction of viruses and shellfish and also to develop efficient methods for inactivating/removing the viruses from this food commodity.…”
mentioning
confidence: 99%
“…UV light treatment has historically been widely utilized by water treatment plants, has also been used for seawater disinfection in depuration tanks (Garcia et al, 2014). Depuration is a process where specific organisms (in this case bivalve mollusks) are placed into a large area or tank of clean water to allow for expulsion and diffusion/removal of any contaminants that may have been present on the organism (in this case viruses) to be removed.…”
Section: Radiation-based Treatmentsmentioning
confidence: 99%
“…This is particularly relevant, as molluscan shellfish are a leading food implicated in human norovirus illness. Garcia et al (2014) investigated the ability of UV to reduce MNV and recombinant human adenovirus artificially seeded into depuration water. Water samples were taken after the treatment and prior to further chemical disinfection (without residual free chlorine).…”
Section: Radiation-based Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation